Partai Buruh dan Kelas Pekerja di Indonesia - Fredick Broven Ekayanta (Journal of Politics and Policy, 2022)
This article discusses the Labor Party’s initiatives to create a political party that represents Indonesia’s working class. Unlike other parties that were formed because of factionalization, internal conflict, or top-down by certain business elites, The Labor Party demonstrates the existence of political parties in Indonesia that were founded as an expression of dissatisfaction with a particular state policy, like Cipta Kerja Bill. Using the method and discourse theory by Ernesto Laclau, this article argues that the Labor Party's founding was initiated by enacting regulation that was seen as the “common enemy” of social organizations. The existence of a common enemy revives the shared awareness and forms the logic of equivalence of having a political party as its own. As a party based on the working class, it creates political frontiers against the government, existing political parties, and oligarchs, which are considered responsible for not fulfilling the demands of the working class in Indonesia.